“New” Muslim Women and the Myth of “Love Jihad”: From Victims to Security Threats - Nidah Kaiser (South Asia Multidisciplinary Academic Journal)
This paper seeks to untangle the intertwined nature of securitization and gendered Islamophobia through the prism of the newly enacted anti-conversion law in Uttar Pradesh, commonly known as the “love jihad” law. The Prohibition of Unlawful Conversion of Religion Act 2021, promulgated by the state of Uttar Pradesh on November 28, 2020, prohibits the religious conversion of individuals or groups by “misrepresentation, force, fraud, undue influence, coercion, allurement or marriage.” The Act legitimizes what has gripped the popular imagination as the myth of “love jihad,” or the conversion of a Hindu woman to Islam through marriage to a Muslim man. Against this background, this paper examines how the state, through the imposition of the law, affixes permanence to the identity of the “new” Muslim woman, not only as a victim but also a security threat to the nation. This paper is based on fieldwork in Uttar Pradesh focusing on four cases of alleged forced conversion. It draws on documentary sources and interviews with multiple stakeholders—“new” Muslim women and their family members, the accused men and their family members, district court defense and prosecution advocates, and civil and women’s rights activists.